COVID-19 Vaccines Development Discord: A Focus on the BRICS and Implications for Africa's Access and Affordability Matters. (3rd April 2021) - Nhamo, Godwell
ABSTRACT: The 17th Sustainable Development Goal seeks to promote partnerships at various levels. To this end, COVID-19 vaccines development partnerships in the BRICS (Brazil, Russia, India, China and South Africa) are inevitable in facilitating ethical access to affordable and safe vaccines the world over. With South Africa being part of the BRICS, its presence can assist in leveraging the partnership to ensure that COVID-19 vaccines developed by the BRICS are efficiently deployed in Africa. Through the tracking of announcements, documents and critical discourse analysis, and Geographical Information Systems, this paper investigates COVID-19 vaccines development collaboration in the BRICS and its implication for Africa. It emerges that there is an inherent discord in the BRICS, with bilateral arrangements both within and outside the forum being evident. This has resulted in advance breakthrough COVID-19 vaccines from China and Russia not widely tried across the BRICS. The paper notes that these developments weaken the global south and affect its potential to develop COVID 19 vaccines. The work recommends a reconsideration in terms of COVID-19 vaccines development and future proofing of collaboration within the BRICS and finding a way of having South Africa continue to lobby for affordable and accessible vaccines for Africa.